Karakterisasi Morfologi dan Isoenzim Aksesi Pamelo [Citrus maxima (Burm.) Merr.] Berbiji dan Tidak Berbiji {Morphological and Isoenzyme Characterization of Seeded and Seedless Pummelo [Citrus maxima (Burm.) Merr.] Accessions} - Rahayu, Arifah; Susanto, Slamet; Purwoko, Bambang Sapto; Dewi, Iswari Saraswati (Jurnal Hortikultura, 2017)
Penelitian ini bertujuan untuk mengevaluasi karakter morfologi dan biokimia dengan isoenzim aksesi pamelo berbiji dan tidak berbiji asal Sumedang, Kudus, Pati dan Magetan. Karakter morfologi yang berperan dalam pengelompokan aksesi pamelo adalah tebal epikarp, pinggiran helai daun, panjang kantong jus, warna kulit buah masak, lebar sayap daun dan bentuk buah, sedangkan karakter isoenzim adalah MDH (Rf 0.11 dan 0.14) dan ACP (Rf 0.24 dan 0.33). Pita ACP Rf 0.24 dapat dijadikan penanda untuk membedakan aksesi berbiji dan tidak berbiji.Â  Dendrogram berdasarkan karakter morfologi memisahkan kelompok aksesi berbiji dan tidak berbiji pada koefisien kemiripan 0.63, dan berdasarkan isoenzim pada koefisien kemiripan 0.49. Dendrogram berdasarkan karakter morfologi dan isoenzim dapat membedakan antara aksesi berbiji, potensial tidak berbiji dan tidak berbiji. Hasil pemetaan komponen utama kongruen dengan dendrogram, yaitu dapat memisahkan aksesi berbiji maupun tidak berbiji, berdasarkan karakter morfologi, isoenzim maupun kombinasinya.KeywordsCitrus maxima (Burm.) Merr.; Morfologi; Isoenzim; Asam fosfatase; Koefisien kemiripanAbstractIndonesia has many pummelo accessions with various shape, size, color, taste, and seeds number of fruit. Up to now characters that can distinguish seeded and seedless pummelo accessions are not yet known well. The objective of this work was to evaluate morphological and biochemical (isoenzyme) characters of seeded and seedless pummelo accessions originated from Sumedang, Pati, Kudus, and Magetan. Morphological identification used vegetative and reproductive component of pummelo tree, based on IPGRI descriptor list. Isoenzyme analysis was done by using young leaves and esterase (EST), malate dehydrogenase (MDH), peroxidase (PER), acid phosphatase (ACP), as well as glutamate oxaloasetate transaminase (GOT) isoenzymes. Morphological characters that contributed in grouping pummelo accessions were epicarp thickness, leaf lamina margin, vesicle length, epicarp color, petiole wing width and fruit shape, while isoenzyme characters were MDH (Rf 0.11 and 0.14) and ACP (Rf 0.24 and 0.33). Fruit shape (pyriform), fruit axis (hollow), seeds number (<10) per fruit, and ACP band at Rf 0.24 could be used as marker to differentiate seeded and seedless pummelo accessions. Separation between seeded and seedless accessions can be done based on morphological characters occured at similarity coefficient of 0.63 while on isoenzyme characters occured at similarity coefficient of 0.49. Dendrogram based on combined morphological and isoenzyme data was able to differentiate seed bearing and seedless pummelo accessions. Principal component analysis results was congruent with that of morphological, isoenzyme, and combination of them.